First Principles Study on the Effect of Pressure on the Structure, Elasticity, and Magnetic Properties of Cubic GaFe(CN)6 Prussian Blue Analogue - Chuankun Zhang; Haiming Huang; Shijun Luo (Applied Sciences, 2019)
The structure, elasticity, and magnetic properties of Prussian blue analogue GaFe(CN)6 under external pressure ranges from 0 to 40 GPa were studied by first principles calculations. In the range of pressure from 0 to 35 GPa, GaFe(CN)6 not only has the half-metallic characteristics of 100% spin polarization, but also has stable mechanical properties. The external pressure has no obvious effect on the crystal structure and anisotropy of GaFe(CN)6, but when the pressure exceeds 35 GPa, the half-metallicity of GaFe(CN)6 disappears, the mechanical properties are no longer stable, and total magnetic moments per formula unit are no longer integer values.